Use of the ESP block as a component of blended anesthesia in abdominal hysterectomy surgeries - А.В. Рижковський (Медицина неотложных состояний)
Background. Fascial plane blocks can provide effective analgesia for abdominal surgeries. The purpose of our study was to assess whether adding erector spinae plane (ESP) block preoperatively could reduce pain after abdominal hysterectomy, compared with no regional analgesia. Materials and methods. We conducted a prospective cohort observational study that included 50 patients aged 40–55 years with complicated symptomatic fibroids. They were divided into 2 groups. Both of them underwent general anesthesia, but the group II additio-nally received ESP block bilaterally. Stages of the study: intraoperative stage (h0), 30 minutes (m30), 6 (h6), 12 (h12), 24 (h24), 48 (h48), 72 hours (h72) after the surgery. We analyzed the pain level, intraoperative need for fentanyl, the daily requirement of morphine, heart rate and mean arterial pressure. Results. It was found that the level of pain according to visual analog scale in the group I reached its maximum values at the stages m30 and h6 and was 6.5 [3.0; 8.5] and 5.5 [3.0; 7.0] points, while in the II group — 4.0 [3.0; 8.5] and 3.0 [2.0; 8.0] points, respectively (p < 0.05). The daily requirement of morphine at the h24 stage was 7.5 [2.5; 7.0] mg/day in the group I, and 5.0 [2.5; 10.0] mg/day in the group II (p < 0.05). There were differences in heart rate between the groups I and II at m30, h6 and h24 stage of study — the values were higher in the group I (p > 0.05). Conclusions. Adding ESP block was associated with a lower need for fentanyl during surgery, pain level, and need for morphine after the surgery.